Characterization of shrouding supersonic gas-solid jet with different center pipe insertion depths and powder flow rates - Ceng Li; Guangsheng Wei; Rong Zhu; Fuhai Liu; Chengjin Han; Linghui Meng (Results in Engineering, 2025)
Lime, as one of the main components of foam slag generation, is often put into the molten pool in the form of lumps, and there are problems such as slower melting and difficulties in deep dephosphorization. This study proposes a central tubular lance design to enhance molten bath dynamics and dephosphorization efficiency. The dual-function configuration maintains oxygen jet impact velocity while injecting lime powder via high-speed gas-solid jets toward the slag-metal interface, optimizing flux utilization efficiency. Numerical modeling of shrouding supersonic gas-solid injection reveals: (1) The jet length of the 25-mm insertion depth nozzle measures approximately 1.6 times that of the 5-mm configuration, with gas-phase velocity attenuation rates decreasing as powder flow increases; (2) Increased insertion depth inversely enhances circumfluent oxygen jet velocity, peaking at 483.2 m/s with 15-mm insertion; central pipe powder primarily affects axial velocity magnitude while exerting minimal impact on circumfluent oxygen jet speed; (3) The region of high TKE is directly proportional to the depth of insertion of the the center pipe and inversely proportional to the rate of powder injection into the the center pipe. These findings will provide a certain theoretical basis for the industrial test of supersonic gas-solid injection of lime powder in EAF, which is of significance for the less-slag efficient smelting of the Tweed iron EAF.